Dental caries characteristics in the first permanent molar in school age children. - Yoel González Beriau; Nora Sexto Delgado; Antonia Francisco Local; Ana Gloria Vázquez de León (Medisur)
Background: Dental caries is one of the main health problems in children. The first permanent molar presents caries more frequently than any other. Objective: To describe the characteristics of dental caries in the first permanent molars in children between 6 and 13 years-old, and to assess oral hygiene and knowledge about the subject in all the patients treated in the stomatology consultation Barrio adentro “El Guapo”, from November 2005 to March 2006. Methods: A descriptive, transversal study showed that most of the patients had dental caries. It was proved that many of them had, at least, on of the first molars affected by dental caries. The quotient first molar affected/ patient was higher than one. Results: There was a decrease in the percentage of healthy permanent first molars. Poor oral hygiene prevailed, with a medium knowledge level on the subject. Most of the parents didn´t know about the first molar dental cavity. Conclusions: It was needed to perform educative tasks aimed at this age group to avoid further damage to this important tooth, central for the development of the stomatognathic system.